Teaching For The Future By Reaching Into The Past - Wilson, Don (Teaching History: A Journal of Methods, 1993)
I am pleased-and flattered-to have such a distinguished and learned audience today. Just think: there are probably more history-minded persons in this room right now than anywhere else in the United States. That is a great credit to the organizers of this conference. Speaking at such an occasion as today’s though, I am reminded of something Winston Churchill once said. A listener asked him, "Doesn’t it thrill you, Mr. Churchill, to know that every time you speak the hall is packed to overflowing?" Sir Winston replied, "It is quite flattering, but whenever I feel this way I always remember that, if instead of making a speech, I was being hanged, the crowd would be twice as big."1